EVALUASI PELAKSANAAN KEBIJAKAN PENDIDIKAN GRATIS PADA JENJANG SEKOLAH MENENGAH DI KABUPATEN SUKOHARJO - Ratna Yuliana; Wiwik Widayati; Achmad Taufiq (Journal of Politic and Government Studies, 2015)
ABSTRACTION THE EVALUATION OF POLICY IMPLEMENTATION OF FREE EDUCATION ON HIGH SCHOOL EDUCATION IN SUKOHARJO DISTRICT The research is motivated because Sukoharjo District as one of regional government in Indonesia applies the free education policy until high school education since 2008. The education fee is too high, hence many people complain. On the otherside, ironically, there are some funds such as BOS, BOP, from APBD and other funding source that is distributed to school, but student’s parent still complain because of the addtional fee from school. This research is made to evaluate the policy implemantationof free education on senior high school education in Sukoharjo district. The research type is qualitative uses descriptive method. Data in this research are taken from collecting data through documentation and in depth interview with key informant which is related to the free education policy which is performed by Department of Education Sukoharjo District and High school education so data are accurate and concrete. The result of the research shows that policy implementation of free education on high school education in Sukoharjo district process is reviewed on resource, communication, disposition and bureaucracy structure. Resource and communication indicator shows at low level, budget resource that is given to school only capable on academic activity and lack of information explanation about the definition of free education to the society. Meanwhile, disposition and breaucracy structure indicator are no problem at all, implementor and policy target have obvious commitment which is supported by cooperation and coordination that clear among government, implementor and school. The result of the analysis above, advices that can be given are policy implementation of free education on high school education need to be supported with concern of these things. 1) The need of budget resource 2) The definition of free education among governmen, department of education and society must be similar, 3) the management mechanism and responsibility free education fund and 4) the succession of free education policy. Keywords : free education policy, high school in Sukoharjo district